Juvenile Justice System in Italy. Research and interventions (2012)
This paper talks about the juvenile justice system in Italy. The author describes the interventions done with minors, boys and girls aged from 14 until 18 years, who have committed offenses of the civil or penal code, by the New Code of Criminal Procedure for Minors (1988). The Procedures have had some positive psychological aspects, aimed to avoid detention, thanks to alternative measures and strategies for inclusion, including also the minors living in the South, that are often involved in mafia-crimes. Nonetheless there are more negative psychological issues, because alternative punishments are not often applied to minors that lack social networks, particularly to foreign ones. Three examples of participatory researches will be shown, promoted by the Municipality of Florence, Department of Psychology and Third Sector Associations, aimed to promote psychological and social inclusion of minors (particularly those coming from abroad), with the commitment of active citizenship organizations, with an evaluation of their strengths and weaknesses.